PENANGANAN PERTAMA PADA BAYI KEJANG DEMAM DI POSYANDU DESA PATEMON - Luluk Fauziyah Januarti (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
Febrile seizures are seizures that occur due to an increase in body temperature (rectal temperature above 38° C) due to an extracranial process without intracranial infection or other causes. Fever seizures often occur in children aged 6 months to 5 years because their immune system is still low in children under five (Wilson, 2016). The incidence of febrile seizures is estimated to be higher in Asia, approximately 20% of cases are complex febrile seizures (Manjoer et al., 2000). According to the Health Profile of Bangkalan Regency (2017), one of the diseases that can cause death in children under five is pneumonia. Peneumonia is a disease that can be caused by viruses and manifests in the presence of fever. Based on a survey through interviews with parents of babies in Patemon Village, information was obtained that many parents of babies in Patemon Village did not know how to properly handle febrile seizures. The method used to carry out community service is by collecting data on the number of parents who have babies in the village of Patemon Bangkalan, then conducting interviews with parents about problems related to awareness and knowledge about handling febrile seizures, then making a time contract with the mother. The activity was continued with a pre-test, audiovisual-based counseling, and training in the management of febrile seizures in infants, the activities were carried out at the Posyandu in Patemon Village. There were 20 participants from Patemon Village who participated in the extension activities. Participants are given a pre test and post test using the instrument based on the material given. Overall, the material presented can be understood by the participants. The results of the activity showed that before being given training, the knowledge of mothers was the same between the enough and insufficient categories, namely 40% and after being given the training, it increased into a good category, namely by 50%.